(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Introduction: During imaging with Single Photon Emission Computed Tomography (SPECT) units, ionizing radiation is emitted by a patient’s body after being injected with radiopharmaceuticals (Rph). Radiation protection as well as knowledge of safe regions around the working environment is essential for nuclear medicine (NM) occupational workers. The present study measured the dose rate at different points around the Rph-injected patients with different activities of 99m Tc-DTPA for renograms and 99mTc-HDP for bone scans, the two most common imaging procedures in the SPECT units of NM establishments. Patients and Methods: This study was carried out in the scintigraphy division of the Institute of Nuclear Medicine and Allied Sciences (INMAS), Kushtia, where 52 male patients were included. Out of the 52 patients, DTPA renogram was done in 26, aging between 1 and 69 (mean = 30.8) years, and bone scan was done in 26, aging between 29 and 71 (mean = 38.8) years. Patients received a dose of 2-5 mCi for the DTPA renogram and 20 mCi for the bone scan with the Mediso SPECT-CT gamma camera unit. The dose rates were measured pragmatically by using a ranger survey meter around radioactive patients in different locations in SPECT-CT units. Result: During contact with radioactive patients, the occupational exposure increases but significantly decreases by increasing distance, as well as the dose rate reduces greatly with respect to time. This study observed that radiation dose was very low at 1 m distance from the radioactive patient. Conclusion: The SPECT/CT occupational worker should remain at a distance of more than 1 m from the radioactive patients and carry TLD batches and wear lead shield aprons for their safety. Bangladesh J. Nuclear Med. 28(1): 130-134, 2024